A Contrastive Analysis of English Novel Memories of My Melancholy Whores and Its Urdu Translation from the Perspective of Rewriting Theory - Abd Ul Waheed (University of Chitral Journal of Linguistics and Literature, 2023)
This study applies André Lefevre’s theory of rewriting to conduct a contrastive analysis between the Urdu translation and the original English version of Gabriel Garcia Marquez’s novel Memories of My Melancholy Whores. Focusing on the perspective of Rewriting theory, the research explores Umer Memon’s Urdu rendition titled Apni Sogwar Beeswaon ki Yaadain as a case study. The analysis reveals that Memon’s Urdu version is a product of rewriting, influenced by theoretical and poetic considerations. The study, anchored in rewriting theory, introduces a fresh approach to understanding contemporary social realism and the translation of romantic novels. By examining the two versions it underscores that translation studies extend beyond linguistic aspects, encompassing macro-level elements like culture and society. This contrastive analysis not only enriches our comprehension of novel translation but also contributes to broader discussions on the translation of contemporary Western social and romantic novels, hoping to inspire further research in this domain.